2020
DOI: 10.21203/rs.2.9614/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual-biased gene expression of olfactory-related genes in the antennae of Conogethes pinicolalis (Lepidoptera: Crambidae)

Abstract: Background: Conogethes pinicolalis (Lepidoptera: Crambidae), is similar to Conogethes punctiferalis (yellow peach moth) and its host plant is gymnosperms , especially for masson pine. So far, less literature was reported on this pest. In the present study, we sequenced and characterized the antennal transcriptomes of male and female C. pinicolalis for the first time. Results: Totally, 26 odorant-binding protein (OBP) genes, 19 chemosensory protein (CSP) genes, 55 odorant receptor (OR) genes and 20 ionotropic r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Oliveira et al [ 101 ] has reported the use of RNAi technique to identify the PBP RproOBP27, involved in sex pheromone detection of Rhodnius prolixus. Identification and molecular characterization of PBPs from multiple insect species, such as Cydia pomonella [ 100 ], Chilo suppressalis [ 102 ], Loxostege sticticalis [ 103 ], and Conogethes pinicolalis [ 104 ] have been reported in recent years. PBP1 from S. exigua [ 105 ] and Cyrtotrachelus buqueti [ 106 ] can also bind to plant volatile compounds, such as benzaldehyde, linalool, indole, and other carboxylic acids, in addition to pheromone molecules.…”
Section: Mechanisms Of Insect Sex Pheromone Perceptionmentioning
confidence: 99%
“…Oliveira et al [ 101 ] has reported the use of RNAi technique to identify the PBP RproOBP27, involved in sex pheromone detection of Rhodnius prolixus. Identification and molecular characterization of PBPs from multiple insect species, such as Cydia pomonella [ 100 ], Chilo suppressalis [ 102 ], Loxostege sticticalis [ 103 ], and Conogethes pinicolalis [ 104 ] have been reported in recent years. PBP1 from S. exigua [ 105 ] and Cyrtotrachelus buqueti [ 106 ] can also bind to plant volatile compounds, such as benzaldehyde, linalool, indole, and other carboxylic acids, in addition to pheromone molecules.…”
Section: Mechanisms Of Insect Sex Pheromone Perceptionmentioning
confidence: 99%